KONSEPSI MAHRAM SEBAB PERZINAAN DALAM HUKUM ISLAM: Kajian Aplikasi Qiyas Dalam Persoalan Larangan Perkawinan Anak Hasil Zina Dengan Ayah Biologisnya - Moch Nurcholis (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2019)
Jurisprudence books divide the concept of marriage into two groups, First, the group that is permissible for marriage. Second, the group that is not allowed or forbidden to be married (mah}ram). The concept is based on the presence or absence of blood relations between the bride and groom. So in the fiqh study mah}ram is divided into three in general namely mah}ram bi nasab, mah}ram bi mus}aharah and mah} ram bi roudlo`. However, there is a relationship where the scholars disagree, namely whether a male adulterer has an affair with a daughter resulting from adultery ?. This is interesting to study considering that both fiqh books and laws in Indonesia have stated that children born outside a legal marriage (both adultery and siri) only have a nasab relationship (mah}ram) with the mother and family of the mother . To answer the problem of whether a male adulterer has a relationship with a daughter of adultery and may or may not get married, the writer will examine the criteria of mah}ram contained in the books of fiqh. After obtaining data about the forms of security, it is then analyzed using the legal excavation method in the form of qiyas. In the qiyas methodology there are stages to finding `illat law. The technique of determining `illat can be done by using two common methods, namely using the theorem naqli and` aqli. So that the 'illat law emerges 'illat similarity between cells of genetic material contained in sperm and milk so as to make both of them a major influence on the mental and physical health of a child born or breastfed that is inherited from the genetic cells of his parents. From these findings, it can be concluded that the marriage between biological father and daughter resulting from adultery is prohibited.